Student Evaluation of Teachers’ Effectiveness (SETE) scale: translation, cross-cultural adaptation and psychometric properties in a Latin American sample - Villar-Guevara, Miluska; Livia-Segovia, José Hector; García-Salirrosas, Elizabeth Emperatriz; Fernández-Mallma, Israel (Frontiers in Education, 2024)
Introduction Teacher effectiveness is a burgeoning field. Those responsible for educational policies seem increasingly committed to this fact, since it is one of the most important factors that influence the success of a university student; for this reason, the study of this topic has gained relevance in recent years. Therefore, an instrument with adequate psychometric properties is needed to measure this construct in Spanish-speaking countries. Objective The study had the purpose of translating, adapting, and evaluating the internal structure, providing evidence of reliability and validity of the Student Evaluation of Teachers’ Effectiveness (SETE) Scale in a Latin American sample. Methods An instrumental study was carried out and through convenience sampling, data were collected from 1,000 university students from South America belonging to a private educational network. The participants were between 18 and 40 years old (M = 21.25, SD = 2.99). Analyzes used Structural Equation Modeling (SEM) with AMOS 24 statistical software. Results Confirmatory Factor Analysis provided a 4-factor, 28-item fit model (CMIN/DF = 4.359; CFI = 0.956; SRMR = 0.030; RMSEA = 0.058). The results demonstrated good internal consistency (α = between 0.927 and 0.961; CR = between 0.927 and 0.962; AVE = between 0.646 and 0.799). Evidence of validity and reliability was obtained for the total sample. Discussion This adaptation and validation of the SETE scale makes it a valid, useful, reliable, and necessary tool that can be considered to evaluate teachers’ effectiveness from the perspective of university students.